A life of joy - Clipston, Amy. (Grand Rapids, MI : Zondervan, 2012)
When she returns for an extended visit to her hometown in Virginia, eighteen-year-old Lindsay Bedford reconnects with old friends and faces family pressures as she tries to decide whether or not to stay in her Amish community.
Keywords: Amish -- Fiction; Amish Country (Pa.) -- Fiction; Christian fiction